Evaluation of Gharraf River Water for different Uses, South Iraq - Al-Dabbas, Moutaz A.; Al-Shamma’a, Ayser M.; Al-Mutawki, Kareem G. (Iraqi Journal of Science, 2018)
Water quality has become an important requirement in recent years, assumed the enormous pressure on water resources. As a result of the rapid population growth and climate change. Seven sampling stations were chosen along the river, specifically near the important cities. After analyzing the water samples, it was found that pH values range from (7.1 to 7.5). The values of total dissolved ions ranged from (730 to 1390) mg/l. It was found that the sodium percentage in the river water samples ranged from (36.8 to 51.3), which is acceptable for irrigation purposes. The water content of magnesium hazard ranges from (45.1 to 48.6), it is within the permissible limits for watering purposes. The residual sodium amounts range from (-4.01 to -2.86) and are within acceptable limits. Water quality index model was used and according to this model classification, it was found that water is good. PHREEQC model was used to identify the geochemical changes of the river water with distance, found that carbonate mineral were under saturation, while clay mineral were in saturation phase.